The use of hyperspectral remote sensing systems in precision agriculture: current status and future trends - Mohd Shafri, Helmi Zulhaidi (Faculty of Engineering, Universiti Putra Malaysia, 2016)
This paper focuses on the use of hyperspectral remote sensing technology in precision agriculture. The types of platforms and sensors as well as the algorithms used in the processing of hyperspectral data for agricultural applications are discussed. Several relevant applications related to the Malaysian agricultural context are also being reviewed. This overview will cover the current status and the future directions in the use of hyperspectral remote sensing technology in precision agriculture.